Marantodes pumilum (Blume) Kuntze (Kacip Fatimah) stimulates uterine contraction in rats in post-partum period - Wan Omar, Wan Fatein Nabeila; Giribabu, Nelli; Karim, Kamarulzaman; Salleh, Naguib (Elsevier, 2019)
thnopharmacological relevance: Marantodes pumilum (Blume) Kuntze has traditionally been used to firm the uterus after delivery, however scientific evidences behind this claim is still lacking. Aims of study: To demonstrate Marantodes pumilum leaves aqueous extract (MPE) has an effect on uterine contraction after delivery and to elucidate the molecular mechanisms involved. Methods: Day-1 post-delivery female rats were given MPE (100, 250 and 500 mg/kg/day) orally for seven consecutive days. A day after the last treatment (day-8), rats were sacrificed and uteri were harvested and subjected for ex-vivo contraction study using organ bath followed by protein expression and distribution study by Western blotting and immunohistochemistry techniques, respectively. The proteins of interest include calmo- dulin-CaM, myosin light chain kinase-MLCK, sarcoplasmic reticulum Ca2+-ATPase (SERCA), G-protein α and β (Gα and Gβ), inositol-triphosphate 3-kinase (IP3K), oxytocin receptor-OTR, prostaglandin (PGF)2α receptor- PGFR, muscarinic receptor-MAChR and estrogen receptor (ER) isoforms α and β. Levels of estradiol and pro- gesterone in serum were determined by enzyme-linked immunoassay (ELISA). Results: Ex-vivo contraction study revealed the force of uterine contraction increased with increasing doses of MPE. In addition, expression of CaM, MLCK, SERCA, Gα, Gβ, IP3K, OTR, PGF2α, MAChR, Erα and ERβ in the uterus increased with increasing doses of MPE. Serum analysis indicate that estradiol levels decreased while progesterone levels remained low at day-8 post-partum in rats receiving 250 and 500 mg/kg/day MPE. Conclusions: These findings support the claims that MPE help to firm the uterus and pave the way for its use as a uterotonic agent after delivery.